Konsep Diri Siswa Slow Learner Di Sekolah Dasar Islam Terpadu Al-Azhar Darul Jannah Bukittinggi - Satria Buana Putra; Dodi Pasila Putra; Deswalantri Deswalantri; Syawaluddin Syawaluddin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research aims to find out the self-concept of slow learner students at SD Al-Azhar Darul Jannah Bukittinggi. The type of research used in this research is field research. The research used is a quantitative descriptive method. Quantitative descriptive is research that attempts to describe or depict a symptom or event that is currently occurring. The instrument used in this research was the litker scale. The population in this study was 22 people, with this population being sampled based on Ivan Fanani Qomusuddin's opinion. The sampling technique used in this research was saturated sampling. The results of this research show that the distribution of data based on the kurtosis value of Slow Learner Students' Self Concept at SD Al-Azhar Darul Jannah Bukittinggi is positive with a relative frequency of 41%, categorized as very good, categorized as good, 39%. Categorized as sufficient 19%. Categorized as not good 1% and categorized as very bad 0%. Self-Concept of Slow Learner Students with positive self-concept at SD Al-Azhar Darul Jannah Bukittinggi where classified as very good at 41%. Negative Self-Concept of Slow Learner Students at SD Al-Azhar Darul Jannah Bukittinggi is positive with a relative frequency of 41%, categorized as very good, categorized as good, 40%. Categorized as sufficient 18%. Categorized as not good at 1% and categorized as very bad at 0%. that the Self-Concept of Slow Learner Students at SD Al-Azhar Darul Jannah Bukittinggi is classified as very good at 41%. Self Concept The Self Concept of Slow Learner Students at SDIT Al-Azhar Darul Jannah Bukittinggi assumes Positive because there is a mean value of 1,096,364 which is greater than the mean value of the Negative concept of 1,090,000. This shows that the self-concept of slow learner students at SDIT Al-Azhar Darul Jannah Bukittinggi is not very significant.